Validation of a Triplex Quantitative Polymerase Chain Reaction Assay for Detection and Quantification of Traditional Protein Sources, Pisum sativum L. and Glycine max (L.) Merr., in Protein Powder Mixtures - Faller, Adam C.; Shanmughanandhan, Dhivya; Ragupathy, Subramanyam; Zhang, Yanjun; Lu, Zhengfei; Chang, Peter; Swanson, Gary; Newmaster, Steven G. (Frontiers in Plant Science, 2021)
Several botanicals have been traditionally used as protein sources, including the leguminous Pisum sativum L. and Glycine max (L.) Merr. While a rich history exists of cultivating these plants for their whole, protein-rich grain, modern use as powdered supplements present a new challenge in material authentication. The absence of clear morphological identifiers of an intact plant and the existence of long, complex supply chains behoove industry to create quick, reliable analytical tools to identify the botanical source of a protein product (many of which contain multiple sources). The utility of molecular tools for plant-based protein powder authentication is gaining traction, but few validated tools exist. Multiplex qPCR can provide an economical means by which sources can be identified and relative proportions quantified. We followed established guidelines for the design, optimization, and validation of qPCR assay, and developed a triplex qPCR assay that can amplify and quantify pea and soy DNA targets, normalized by a calibrator. The assay was evaluated for analytical specificity, analytical sensitivity, efficiency, precision, dynamic range, repeatability, and reproducibility. We tested the quantitative ability of the assay using pea and soy DNA mixtures, finding exceptional quantitative linearity for both targets — 0.9983 (p<0.0001) for soy and 0.9915 (p<0.0001) for pea. Ratios based on mass of protein powder were also tested, resulting in non-linear patterns in data that suggested the requirement of further sample preparation optimization or algorithmic correction. Variation in fragment size within different lots of commercial protein powder samples was also analyzed, revealing low standard deviation among lots. Ultimately, this study demonstrated the utility of qPCR in the context of protein powder mixtures and highlighted key considerations to take into account for commercial implementation.